Spectroscopy of the solid solutions (Si₂)₁₋x(ZnS)x - Sapaev, B.; Saidov, A.S.; Bacherikov, Yu.Yu.; Konakova, R.V.; Okhrimenko, O.B.; Dmitruk, I.N.; Galak, N.P.; Sapaev, I.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Presented are the investigation of (Si₂)₁₋x(ZnS)x solid solutions. Morphological, electrical, and optical properties of the solutions are investigated. Chemical components of the solid solutions are homogeneously distributed along the thickness of the layer. The photoluminescence spectra of (Si₂)₁₋x(ZnS)x consist of a wide band with the peak within the range of 505 to 520 nm. The Raman scattering shows that approximately 19 % of silicon located directly under the epitaxial film is in amorphous phase.